2012
DOI: 10.1103/physreva.86.053817
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependence and passive drains in fish-eye lenses

Abstract: The Maxwell fish eye lens has previously been reported as being capable of the much sought after phenomenon of subwavelength imaging. The inclusion of a drain in this system is considered crucial to the imaging ability, although its role is the topic of much debate. This paper provides a numerical investigation into a practical implementation of a drain in such systems, and analyzes the strong frequency dependence of both the Maxwell fish eye lens and an alternative, the Miñano lens. The imaging capability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…The first important conceptual point we make concerns the sources and detectors. In the context of the controversy on perfect imaging, finding a simple, practical model for detectors has been a long-outstanding problem [9,15,17,[27][28][29][30]. Usually a source was assumed to be a predetermined current that generates electromagnetic waves, a detector was modelled as a drain.…”
mentioning
confidence: 99%
“…The first important conceptual point we make concerns the sources and detectors. In the context of the controversy on perfect imaging, finding a simple, practical model for detectors has been a long-outstanding problem [9,15,17,[27][28][29][30]. Usually a source was assumed to be a predetermined current that generates electromagnetic waves, a detector was modelled as a drain.…”
mentioning
confidence: 99%
“…The pole at zero frequency, evident in the longitudinal part of the Green function (4), does not contribute, because we have assumed condition (7). Equation (9) means that the electric field reduces to a sum over the eigenmodes of the cavity after the current has been switched off ( Δ > + t t t 2 0 0 ), with each eigenmode weighted by the corresponding Fourier component of the source…”
Section: Electromagnetic Radiation From a Source In A Cavitymentioning
confidence: 99%
“…The use of an active current element to concentrate the electromagnetic field was recently the subject of debate in the context of imaging [4][5][6][7][8][9][10], where it was claimed that the sub-wavelength scale of the field around an active drain could be used to resolve small features of a distant object within the Maxwell fish-eye lens. Although it now seems unlikely that a useful imaging device can be made in this way [9], the device proposed in [4] has other interesting properties. In particular, Tyc and Danner [12] have shown that absolute optical instruments 4 tend to have a nearly uniform spacing of eigenfrequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The subwavelength focusing is due to the drain in MFEL/MFEM but not the medium itself [4,5,10]; if there are some additional passive drains around the imaging point, they will greatly influence the imaging effect (e.g., we may also get a focused spot at other drains that are not located at the image point) and an MFEM cannot give a super-resolution imaging if there are some other drains around the imaging points [9,11,17].…”
Section: Introductionmentioning
confidence: 99%
“…Leonhardt claimed that Maxwell's fish eye lens (MFEL), which can provide ideal imaging from the perspective of geometric optics, can also provide perfect imaging from the perspective of wave optics (i.e., the resolution can be infinite theoretically). He also proposed that a 2D Maxwell's fish eye mirror (i.e., a Maxwell's fish eye lens enclosed by a mirror) could theoretically provide perfect imaging, which has been an intense subject of controversy [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Blaikie commented that the super-resolution is due to the active drain at the image point but not the property of the lens [4], and hence many other types of imaging system can also achieve such subwavelength focusing with the help of a drain, e.g., we can obtain a sub-wavelength focused spot at the image point if there is only one drain exactly located at the image point in any absolute image system (such as a mirror-enclosed elliptical cavity filled with air when a line current is at one focus and a drain is exactly located at the other focus [5]).…”
Section: Introductionmentioning
confidence: 99%